Adolescent gullibility towards advertisements - Hoe, Angela Li Ling (2008)
This project examines the factors influencing adolescent gullibility towards advertisements.The motive of this study is to enable advertisers to make better use of their advertising dollars. In addition, it aims to aid government in its deliberations regarding the need for regulation in the advertising industry in order to protect adolescents from misleading advertisements.